Pramlintide, an antidiabetic, is antineoplastic in colorectal cancer and synergizes with conventional chemotherapy - Al-Keilani MS; Alsmadi DH; Darweesh RS; Alzoubi KH (Dove Medical Press, 2018)
Maha S Al-Keilani,1 Dua H Alsmadi,1 Ruba S Darweesh,2 Karem H Alzoubi1 1Department of Clinical Pharmacy, College of Pharmacy, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Pharmaceutical Technology, College of Pharmacy, Jordan University of Science and Technology, Irbid, Jordan Background: Approximately 90% of patients with metastatic colorectal cancer fail therapy mainly due to resistance. Taking advantage of currently approved agents for treatment of disease conditions other than cancer for the identification of new adjuvant anticancer therapies is highly encouraged. Pramlintide is a parenteral antidiabetic agent that is currently approved for treatment of types 1 and 2 diabetes mellitus.Objectives: To address the antineoplastic potential of pramlintide in colorectal cancer and to evaluate the ability of pramlintide to enhance the cytotoxicity of 5-fluorouracil, oxaliplatin, and irinotecan against colorectal cancer cell lines expressing wild-type and mutant p53.Materials and methods: The antiproliferative effect of pramlintide alone or in combination with 5-fluorouracil, oxaliplatin, or irinotecan in HCT-116 and HT-29 colorectal cancer cell lines was investigated using MTT cell proliferation assay. IC50 values were calculated using Compusyn software 1.0. Synergy values (R) were calculated using the ratio of IC50 of each primary drug alone divided by combination IC50s. For each two pairs of experiments, Student’s t-test was used for analysis. For combination studies, one-way analysis of variance and Tukey post hoc testing was performed using R 3.3.2 software. A p-value of <0.05 was considered significant.Results: Pramlintide inhibited the growth of HCT-116 and HT-29 in a dose-dependent manner, with higher efficacy against the latter (IC50s; 48.67 and 9.10 µg/mL, respectively; p-value =0.013). Moreover, the addition of 5, 10, and 20 µg/mL of pramlintide to HCT-116 and HT-29 with 5-fluorouracil, oxaliplatin, or irinotecan induced the antiproliferative effect synergistically (R>1.6, p-value <0.05).Conclusion: Pramlintide enhances the cytotoxicity of conventional chemotherapy against colorectal cancer cell lines harboring wild-type or mutant p53. Thus, pramlintide is a promising potential adjuvant chemotherapy in colorectal cancer. Keywords: colorectal cancer, resistance, amylin analog, pramlintide, adjuvant chemotherapy, synergism